ANALISIS HUKUM PENGADAAN PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA PPPK DI INDONESIA - Indah permata, Indah (Indragiri Law Review, 2024)
The implementation of Government Employees with Work Agreements (PPPK) in Indonesia has become an important alternative in recruiting staff to meet the workforce needs in the public sector. However, despite PPPK's strategic role in providing public services, various legal issues need serious attention, particularly in terms of legal protection, equal opportunities, and the selection mechanisms. This study aims to analyze the policy of PPPK recruitment, explore the legal issues related to the rights and employment status of PPPK, and provide recommendations for improving the existing policy. Using a descriptive-analyticalapproach, this study evaluates the regulations governing PPPK, including Ministerial Regulation No. 28 of 2021 and Law No. 5 of 2014 on the State Civil Apparatus. The results of the study indicate that, although the PPPK selection is conducted with a more transparent system, there are still disparities in social protection rights, such as pension entitlements, and unequal access to selection processes in certain regions. Additionally, corruption, collusion, and nepotism (KKN) remain challenges in the PPPK recruitment process. This study recommends the need for improving legal protection for PPPK, including granting pension rights, and enhancing the supervision of the selection process to prevent KKN practices. With a more inclusive and fair policy, it is expected that PPPK can work more productively, feel more valued, and provide high-quality public services